2021
DOI: 10.1155/2021/3237342
|View full text |Cite
|
Sign up to set email alerts
|

A Job‐Shop Scheduling Problem with Bidirectional Circular Precedence Constraints

Abstract: This paper introduces a job-shop scheduling problem (JSP) with bidirectional circular precedence constraints, called BCJSP. In the problem, each job can be started from any operation and continued by its remaining operations in a circular precedence-relation chain via either a clockwise or counterclockwise direction. To solve BCJSP, this paper proposes a multilevel metaheuristic consisting of top-, middle-, and bottom-level algorithms. The top- and middle-level algorithms are population-based metaheuristics, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…To overcome such a drawback, many applications use upperlevel algorithms to control parameters of their solutionsearching algorithms [11,12,14,15,[28][29][30][31]. Some of them, e.g., [5], require more than two levels of algorithms for very complicated problems; however, most of them require only two levels. For solving JSP, there are two two-level metaheuristics acting as adaptive iterated local search algorithms [11,12].…”
Section: Previous Relevantmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome such a drawback, many applications use upperlevel algorithms to control parameters of their solutionsearching algorithms [11,12,14,15,[28][29][30][31]. Some of them, e.g., [5], require more than two levels of algorithms for very complicated problems; however, most of them require only two levels. For solving JSP, there are two two-level metaheuristics acting as adaptive iterated local search algorithms [11,12].…”
Section: Previous Relevantmentioning
confidence: 99%
“…To complete each job, all of its operations must be processed in the sequence from the first to the last operations. JSP has many variants and related problems, such as [4][5][6][7]. One of the well-known variants of JSP is the job-shop scheduling problem with multipurpose machines (MPMJSP) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheduling is a decision-making process in which resources and jobs are allocated efficiently under predetermined scheduling goals to meet production constraints [2]. Over the past 60 years, there has been increasing attention on the job shop scheduling problem because of more complex manufacturing systems and personalized market needs.…”
Section: Introductionmentioning
confidence: 99%
“…Although AI algorithms are capable of generating scheduling strategies with good performance in real time from the overall perspective of the production process of the manufacturing system, the existing literature indicates a lack in studies that have reported the ability to reduce or eliminate the unfavorable impact of randomness at the moment of job release on the operation process of the manufacturing system. For instance, Pisut [2] assumed that the moment of job arrival was the same when constructing the model. In addition, the model constructed using AI algorithms is data driven, and the real time update of historical data is an essential driving factor in ensuring that the constructed model continually exhibits high predictive performance.…”
Section: Introductionmentioning
confidence: 99%